Digital literacy, creativity, and digital entrepreneurship interest among generation z: The mediating role of entrepreneurial mindset - Mardlatillah Romadoni Nur Indraswari, Violeta; Wulandari, Puteri Pekerti; Fauzan, Muhammad (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2026)
The rapid growth of Indonesia's digital economy presents vast opportunities, yet youth entrepreneurial participation remains suboptimal. This study aims to investigate the influence of digital literacy and creativity on digital entrepreneurship interest among Generation Z students at UIN Palangka Raya, with entrepreneurial mindset as a mediating variable. A quantitative research design was employed, collecting data from 100 students through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results indicate that digital literacy has a positive and significant impact on both entrepreneurial mindset and digital entrepreneurship interest. Conversely, creativity does not significantly influence the entrepreneurial mindset. Mediation analysis reveals that the entrepreneurial mindset significantly mediates the relationship between digital literacy and entrepreneurship interest, but fails to mediate the effect of creativity. The study concludes that higher education institutions must prioritize fostering a strategic entrepreneurial mindset and digital literacy over mere creative output to effectively bridge the gap between digital potential and actual career intentions in the creative economy sector.